Two different spectrophotometric methods for simultaneous determination of binary mixture of atenolol and amlodipine in commercial formulation - Omer, Shilan; Yassin Mohammad, muharam; Abdullah, mohammad (Zanco Journal of Pure and Applied Sciences, 2022)
For the simultaneous determination of a binary mixture of amlodipine (AM) and atenolol (AT) in tablets, two approaches were accessible. The first method is the second derivative of the ratio spectra (2DD) that obtained via dividing the absorption spectra of binary mixtures by a standard spectrum of one of the components and then the second derivative of the ratio spectra were calculated. The extended ratio subtraction method (EXRSM) is the second approach, which launches with the ratio subtraction method coupled with 4th derivative spectrophotometry. The calibration curve is linear over the concentration range (2-45) μg/mL and (5-60) μg/mL for amlodipine and atenolol successively. The presented methods have been successfully applied to estimate binary mixtures of amlodipine and atenolol tablets simultaneously and also was satisfactory compared with standard method (HPLC). References ALI, N., ABDELWAHAB, N., EL-FATATRY, H. & OSMAN, W. 2013. Spectrophotometric methods for simultaneous determination of two hypouricemic drugs in their combined dosage form. Pharm Anal Acta, 4, 2-8. ALIZADEH, N. & HEMATI, F. 2014. Spectrophotometric method for the determination of amlodipine besylate in pure and dosage forms using 7, 7, 8, 8-tetracyanoquinodimethane and tetracyanoethylene. Bulletin of Faculty of Pharmacy, Cairo University, 52, 109-114. BLANCO, M., GENÉ, J., ITURRIAGA, H. & MASPOCH, S. 1987. Application of a photodiode array detector to multi-component determination by flow injection analysis. Analyst, 112, 619-622. ÇELEBIER, M., KAYNAK, M. S., ALTıNÖZ, S. & SAHIN, S. 2010. HPLC method development for the simultaneous analysis of amlodipine and valsartan in combined dosage forms and in vitro dissolution studies. Brazilian Journal of Pharmaceutical Sciences, 46, 761-768. COMMISSION, B. P. 2008. British pharmacopoeia 2009, Stationery Office (UK). DARWISH, H., METWALLY, F. H. & EL BAYOUMI, A. 2015. Novel ratio subtraction and isoabsorptive point methods for determination of ambroxol hydrochloride and doxycycline in their combined dosage form: Development and validation. Tropical journal of pharmaceutical research, 14, 133-140. DARWISH, H. W., HASSAN, S. A., SALEM, M. Y. & EL-ZEANY, B. A. 2013. Sequential spectrophotometric method for the simultaneous determination of amlodipine, valsartan, and hydrochlorothiazide in coformulated tablets. International journal of spectroscopy, 2013. DARWISH, H. W., HASSAN, S. A., SALEM, M. Y. & EL-ZEINY, B. A. 2011. Three different spectrophotometric methods manipulating ratio spectra for determination of binary mixture of Amlodipine and Atorvastatin. Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy, 83, 140-148. EL-BARDICY, M. G., LOTFY, H. M., EL-SAYED, M. A. & EL-TARRAS, M. F. 2008. Smart stability-indicating spectrophotometric methods for determination of binary mixtures without prior separation. Journal of AOAC International, 91, 299-310. EL-GINDY, A., EL-ZEANY, B., AWAD, T. & SHABANA, M. M. 2001. Spectrophotometric determination of trifluoperazine HCl and isopropamide iodide in binary mixture using second derivative and second derivative of the ratio spectra methods. Journal of pharmaceutical and biomedical analysis, 26, 203-210. ELGAWISH, M. S., MOSTAFA, S. M. & ELSHANAWANE, A. A. 2011. Simple and rapid HPLC method for simultaneous determination of atenolol and chlorthalidone in spiked human plasma. Saudi Pharmaceutical Journal, 19, 43-49. ELZANFALY, E. S., HASSAN, S. A., SALEM, M. Y. & EL-ZEANY, B. A. 2015. Different signal processing techniques of ratio spectra for spectrophotometric resolution of binary mixture of bisoprolol and hydrochlorothiazide; a comparative study. Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy, 140, 334-343. ISSA, Y. M., ZAYED, S. I. & HABIB, I. H. 2011. Simultaneous determination of ibuprofen and paracetamol using derivatives of the ratio spectra method. Arabian Journal of Chemistry, 4, 259-263. KANNAPPAN, V. & MANNEMALA, S. S. 2016. Simultaneous enantioseparation and purity determination of chiral switches of amlodipine and atenolol by liquid chromatography. Journal of pharmaceutical and biomedical analysis, 120, 221-227. KASTURE, A. & RAMTEKE, M. 2006. Simultaneous UV-spectrophotometric method for the estimation of atenolol and amlodipine besylate in combined dosage form. Indian journal of pharmaceutical sciences, 68. LAMIE, N. T. 2015a. Simultaneous determination of binary mixture of amlodipine besylate and atenolol based on dual wavelengths. Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy, 149, 201-207. LAMIE, N. T. 2015b. Spectrophotometric Methods for Simultaneous Determination of Amlodipine Besylate and Atenolol in Their Tablet Dosage Form. 光谱学与光谱分析, 35, 3538-3543. LAWSON, G., COCKS, E. & TANNA, S. 2012. Quantitative determination of atenolol in dried blood spot samples by LC–HRMS: a potential method for assessing medication adherence. Journal of Chromatography B, 897, 72-79. LOTFY, H. M. & HAGAZY, M. A.-M. 2012. Comparative study of novel spectrophotometric methods manipulating ratio spectra: an application on pharmaceutical ternary mixture of omeprazole, tinidazole and clarithromycin. Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy, 96, 259-270. MOHAMMAD, M. Y., ABDULLAH, M. S. & SABIR, S. S. 2019. Simultaneous Determination of Atenolol and Amlodipine Using Second Derivative Spectroscopy. Polytechnic Journal, 9, 25-29. MOUSSA, B. A., EL-ZAHER, A. A., MAHROUSE, M. A. & AHMED, M. S. 2013. Simultaneous determination of amlodipine besylate and atorvastatin calcium in binary mixture by spectrofluorimetry and HPLC coupled with fluorescence detection. Analytical chemistry insights, 8, ACI. S12921. NEELIMA, M. S., GANDHI, B. M., RAJU, V. B., SUMANTH, K. S., SRINIVAS, K., MOUNIKA, P. & LAKSHMI, P. J. N. 2016. DEVELOPMENT AND VALIDATION OF STABILITY INDICATING REVERSE PHASE HIGH‑PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR SIMULTANEOUS ESTIMATION OF ATENOLOL, HYDROCHLOROTHIAZIDE AND LOSARTAN IN BULK AND PHARMACEUTICAL DOSAGE FORM. DEVELOPMENT, 9. NEVADO, J. B., CABANILLAS, C. G. & SALINAS, F. 1992. Spectrophotometric resolution of ternary mixtures of salicylaldehyde, 3-hydroxybenzaldehyde and 4-hydroxybenzaldehyde by the derivative ratio spectrum-zero crossing method. Talanta, 39, 547-553. OMER, S. A. & FAKHRE, N. A. 2019. Three different spectrophotometric methods for simultaneous determination of pyriproxyfen and chlorothalonil residues in cucumber and cabbage samples. Journal of Spectroscopy, 2019. OSMAN, R. A. M. & ELBASHIR, A. A. 2017. A high-performance liquid chromatographic (HPLC) method for the determination of amlodipine drug in dosage form using 1, 2-naphthoquine-4-sulfonate (NQS). J Anal Pharm Res, 6, 00163. PAWAR, P., MANE, B., AUTI, S. M. & TRIVEDI, V. V. 2013. Simultaneous estimation of amlodipine besylate and atenolol in combined dosage form by Vierodt’s method using UV spectroscopy. PharmaChemica, 5, 97-102. PRASHANTH, K. N. & BASAVAIAH, K. 2012. Sensitive spectrophotometric determination of atenolol in pharmaceutical formulations using bromate-bromide mixture as an Eco-friendly brominating agent. Journal of Analytical Methods in Chemistry, 2012. SALINAS, F., NEVADO, J. B. & MANSILLA, A. E. 1990. A new spectrophotometric method for quantitative multicomponent analysis resolution of mixtures of salicylic and salicyluric acids. Talanta, 37, 347-351. SPANAKIS, M. & NIOPAS, I. 2013. Determination of atenolol in human plasma by HPLC with fluorescence detection: validation and application in a pharmacokinetic study. Journal of chromatographic science, 51, 128-132. SURESH, P., BABU, B. H. & CHAKRAVARTHY, I. 2015. UV-absorbance difference method for simultaneous estimation of atenolol and amlodipine besylate in combined dosage forms. Der Pharm. Lett, 7, 280-284. VAIKOSEN, E. N., BIOGHELE, J., WORLU, R. C. & EBESHI, B. U. 2020. Spectroscopic Determination of Two Beta-Blockers–Atenolol and Propanolol by Oxidative Derivatization Using Potassium Permanganate in Alkaline Medium. Reviews in Analytical Chemistry, 39, 56-64. YILMAZ, B. 2010. Determination of atenolol in pharmaceutical preparations by gas chromatography with flame ionization and mass spectrometric detection. Analytical letters, 43, 2311-2317.